Validity and Reliability of Quality of Nursing Work Life Instrument for Hospital Nurses - Utami Utami; Hari Kusnanto; Bagus Riyono; Syahirul Alim (Jurnal Ners, 2018)
Introduction: The validity and reliability of the quality of nursing work life (QNWL) instrument in hospitals that suitable to treatment needs include: trust, care, respect, learn, and contribute need, have to be assessed. Therefore, in order to perform good care, it is necessary to notice QNWL aspect, which the implementation may be assessed by using valid and reliable instruments. This study aimed to evaluate the construct validity of the QNWL scale in hospital.Methods:  The research used a cross-sectional approach and the respondents were 100 experts in nursing and 400 nurses working in four hospitals in Gresik, Indonesia, who have been working for minimum one year. The sampling technique was purposive sampling. We analyzed the data using content analysis, the validity of item discrimination using Pearson products moment, reliability with Cronbach’s alpha, and construct validity with Confirmatory Factor Analysis.Results: The results based on content validity index QNWL instrument was 0.2075-0.915, with an average 0.7059 (high). Item discrimination capacity was 0.339-0.79 (high), while the reliability was 0.9374 (very high) and the validity of the construct meets the goodness of fit criteria.Conclusion: All constructs are able to explain and support the QNWL instrument model. This research can be used to measure the quality of work life of nurses in all classes of hospitals in Indonesia.